Experiment and analysis on mechanical properties of Artemisia selengensis stalk - Yinyan, Shi; Man, Chen; Xiaochan, Wang; Yongnian, Zhang; Odhiambo, Morice O. (International Journal of Agricultural and Biological Engineering, 2017)
The technology used for the storage and transportation of Artemisia selengensis is becoming increasingly important with its increasing consumption and demand; moreover, the amounts of artificial planting contribute to the challenges in Artemisia selengensis harvesting. Therefore, the mechanical property parameters of the Artemisia selengensis stalks were determined and researched to reduce the mechanical damage during harvesting, transportation, processing and storage. The Artemisia selengensis stalks were taken as the test object and a physical test method was adopted to study the impact of different positions, diameters, and directions on the mechanical properties by using the TMS-Pro texture analyzer; then, the relevant changing trends of the characteristic mechanical parameters were analyzed using statistical software. In the compression test, the compression load-deformation curve was observed and the breaking force and deformation were obtained; then, the compressive strength, elastic modulus and compression energy were computed. Next, the curve-fitting of the compressive strength and compression energy was carried out. In the shear test, the shear stress-deformation curve was obtained and the shear force, deformation, shear strength, and shear work were calculated. Then, the regression fitting of the section area, peak shearing stress and shearing work was conducted. Finally, in the last bending test, the bending stress-deformation curve, bending peak force, deformation, and bending work were obtained. Then the bending forces of other plants were tested, the results were compared and analyzed with the theoretical values, and finally the regression fittings were implemented. All the analysis results showed that Artemisia selengensis stalks can be considered to be anisotropic materials. The results also showed that the compressive strength and elastic modulus decreased with the height of stalk position, while the deformation increased. In addition, with the increase in the stalk diameter, the bending strength and fracture mechanical work increased, while the deformation decreased. The research results can provide a theoretical basis and reference for the design of the harvest equipment of Artemisia selengensis while minimizing its mechanical damage.Keywords: Artemisia selengensis, stalks, texture analyzer, mechanical propertiesDOI: 10.3965/j.ijabe.20171002.2660Citation: Shi Y Y, Chen M, Wang X C, Zhang Y N, Odhiambo M O. Experiment and analysis on mechanical properties of Artemisia selengensis stalk. Int J Agric & Biol Eng, 2017; 10(2): 16–25.